Politik Islam: Analisis Pemikiran Ibn BÄjjah Dalam KitÄb TadbÄ©r Al-Mutawahhid - Kohar, Abdul (Politea : Jurnal Politik Islam, 2020)
Ibn BÄjjah was the first Muslim philosopher in Spanish. His full name is AbÅ« Bakr Muhammad ibn yahya al-ShÄ'igh al-TujÄ©bÄ© al-SaraqustÈ‹. Ibn BÄjjah is also known by the laitin name Avempace, he is a rationalist philosopher. Many of his ideas about political, especially in the book of TadbÄ©r al-Mutawaá¸¥á¸¥id. Ibn BÄjjah said that a government have to be mutawaá¸¥á¸¥id, and mutawaá¸¥á¸¥id should be able to control themselves and be able to control lust, not to be dragged into the mainstream of society. The purpose of this research first the writer wants to say that the government (leader) is a transformation for his society, then democratic systems isnâ€™t just saying "from the society to the society", but democracy have to be motivated by the society who have common sense, wich isnâ€™t appear on personal interests, more precisely good society will produce good leaders. This type in this research is a library research by presenting qualitative-interpretative data, where the main object is the available library books, certainly the books are related to the subject of this research. This research uses two data sources, namely primary and secondary data. The primary data in this research were obtained books written by Ibn BÄjjah's books (kitÄb) such as the Book of TadbÄ©r al-Mutawaá¸¥á¸¥id and RisÄlah al-IttishÄl. While the secondary data is journal, the articles are also bookâ€™s that discuss Ibn BÄjjah in particular. The result of this paper is that the essence of the State's purpose is identical with the purpose of human life. Nations and peoples are united in their pursuit of happiness.